1998
DOI: 10.1046/j.1365-2133.1998.02396.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity of bullous pemphigoid (BP) autoantibodies against the NC16A and C-terminal domains of the 180 kDa BP antigen (BP180): immunoblot analysis and enzyme-linked immunosorbent assay using BP180 recombinant proteins

Abstract: The 180 kDa bullous pemphigoid (BP) antigen (BP180) is known to be recognized by sera from patients with BP, herpes gestationis (HG) and cicatricial pemphigoid (CP). A series of previous studies using BP180 recombinant proteins has shown that most sera from patients with BP and HG react with the NC16A domain of BP180, an extracellular non-collagenous region just adjacent to the plasma membrane. In contrast, the C-terminal region of BP180 has been reported to be one of the epitopes of CP. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
65
3
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 10 publications
9
65
3
5
Order By: Relevance
“…Using rCol15 as antigen, we showed that approximately one-third of the tested autoimmune sera contained either IgG or IgA reactive with it. This is in contrast to previous studies with mainly bacterial recombinant fragments, which found most immunodominant epitopes in the NC16a domain (25,49,50), some in the distal amino-and carboxyl-terminal regions of the molecule, but none in the Col15 domain (23,28,51). By affinity adsorbing the rCol15-reactive immunoglobulins from the patient sera, we also showed that the circulating autoantibodies against rCol15 target collagen XVII at the epidermal basement membrane zone in situ.…”
Section: Discussioncontrasting
confidence: 52%
“…Using rCol15 as antigen, we showed that approximately one-third of the tested autoimmune sera contained either IgG or IgA reactive with it. This is in contrast to previous studies with mainly bacterial recombinant fragments, which found most immunodominant epitopes in the NC16a domain (25,49,50), some in the distal amino-and carboxyl-terminal regions of the molecule, but none in the Col15 domain (23,28,51). By affinity adsorbing the rCol15-reactive immunoglobulins from the patient sera, we also showed that the circulating autoantibodies against rCol15 target collagen XVII at the epidermal basement membrane zone in situ.…”
Section: Discussioncontrasting
confidence: 52%
“…16 ELISA analysis using recombinant COL17 NC16A demonstrated that 94-96% of BP sera reacts to COL17 NC16A peptides. 18,19 In addition, several major antigenic sites have been identified within the N-terminal 45 amino acid stretch of NC16A, while the remaining 28 amino acids of NC16A were shown to have no BP-associated epitopes. 17 Several studies have confirmed that the serum levels of anti-COL17 NC16A autoantibodies correlate with the disease severity of BP.…”
Section: Major Pathogenic Autoantigen: Type XVII Collagen (Col17)mentioning
confidence: 99%
“…16,17 Recently, it has been established that most BP serum samples react with the NC16A domain of BP180. 12,22,23 The purpose of this study was to test the hypothesis that the level of IgG reactivity to NC16A reflected disease severity in patients with BP. Fifteen consecutive patients were analyzed: 9 patients were treated with dapsone-prednisolone, and 6 patients received doxycycline-niacinamide.…”
Section: Commentmentioning
confidence: 99%